Metode Jarh wa al-Ta’dil Kelompok Mutashaddid dan Mutasahil (Telaah Pemikiran Yahya ibn Ma‘in dan al-Turmudhi Perspektif Sosiologi Pengetahuan) - Ahmad Irsyad Al Faruq; Lukman Zain; Ahmad Faqih Hasyim (UIN Siber Syekh Nurjati Cirebon, 2018)
Jarh wa al-Ta’dil is one of important sience in ‘ulum al-hadith. It is because by this science, we can determine the status of rawi, whether their riwayah can be accepted or not. But, the statements of a critic (naqid) to rawi are different. There are three categories of them, called mutashaddid, mutawassit, and mutasahil. Those different categories, of course, did not just appear. Those appeared because of sosio-historical context. Yahya ibn Ma’in and al-Turmudhi are two ciritcs of hadis who represent mutashaddid and mutasahhil. The analysis implementation of Peter L Berger’s knowledge sociology toward the consept of jarh wa al-ta’dil of Yahya ibn Ma’in an al-Turmudhi makes a conclusion that both of their thought about jarh wa al-ta’dil as the both sides of sosio-hisorical conditions and their individual attitude on it. This case is based on three knowledge sociology dialectics process of Peter Berger, including externalisation, objectivation, and internalization. The externalisation process is influenced by; a) the government conditions, b) the scientific development, c) ‘ulum al-hadith, d) jarh wa al-ta’dil, and e) the relationship with their teachers. Whereas, the objectifation dan internalization process influenced by; a) their attitude to the government, b) language (alfaz) and works, and c) their tendencies caused by their teachers’s influence.